The Pengaruh Perlakuan Impregnasi dengan MEG dan PEG Terhadap Warna Kayu Jati Solomon - Dirna, Fitria Cita (Forestry Faculty of Hasanuddin University, 2024)
The color of wood is an important indicator that can be used for assessing the quality of wood, particularly for decorative product applications. This research aims to analyze the results of color changes in Solomon teak wood with impregnation modification (0.5 bar of vacuum for 60 minutes and 2.5 bar pressure for 120 minutes) using the impregnants monoethylene glycol (MEG) and polyethylene glycol (PEG). The Solomon teak wood used measures 2 cm x 5 cm x 10 cm, with a total of five repeated samples. The research results indicate that the treatment with PEG resulted in greater changes in brightness and color compared to aquades and MEG. The effect of impregnation with PEG and MEG on color change falls into the large category, while the category for wood impregnated with aquades is moderate.